Network and security issues for internet mobile entertainment. (Electronic Library., 2004)
We have not seen an Internet-based game that can be identified with the arrival of Internet gaming for the masses. Due to the foundational structure of the Internet, there probably will not be one anytime soon. The problem is that the underlying Internet protocol, IPv4, has not had a major update since its introduction in the early 1970s. Fortunately, in the mid-1990s the standards-based Internet Engineering Task Force began addressing IPv4's deficiencies. The result of these efforts is a new version of IPv4 called IPv6. IPv6's entry will present the Internet gaming community with many opportu.